SEXIST LANGUAGE IN VIRGINIA WOOLF NOVEL MRS DALLOWAY (CRITICAL DISCOURSE ANALYSIS) - Poetryku Syahara Noh; Elisa Nurul Laili; Marginingsih Marginingsih (Universitas Duta Bangsa Surakarta, 2022)
The use of language as a medium of daily communication is only as a tool to facilitate language understanding without realizing that there is an element of discrimination against a particular gender. Sexist language is often found in novels that demonstrated to real life where people associate and deal with stereotypes in society. This research proposes to explain and describe the sexist language types of the main characters found in Mrs. Dalloway novel based on theory of Sara Mills. The research used a qualitative method by applying a critical discourse analysis. The words, phrases, and sentences from monologues and dialogues reflecting sexism in the novel become the data of the research. Data collection techniques used library techniques, namely documents. The data analysis technique used data reduction, data display, and verification techniques. The results of this research show that Sara Mills sexism theory categorizes sexist language into overt and covert sexism. In Mrs. Dalloway novel, there are four types that are consisted of overt sexism: naming, dictionaries, generic pronouns and nouns, and non-parallel terms. For the covert sexism, there are two types in the novel: presuppositions and metaphor.